A Virtual-Reality, 360-Degree Fly-Through of an Arteriovenous Malformation Resection: 2-Dimensional Operative Video. Issue 1 (15th April 2019) - Steinberger, Jeremy; Nistal, Dominic; Schlachter, Leslie; Costa, Anthony; Oemke, Holly; Bederson, Joshua B
Abstract: The application of navigation integrated virtual reality (VR) in neurosurgery is an emerging paradigm that may offer improved situational awareness for the surgeon. Here, we present a case of a complex arteriovenous malformation (AVM) with complex venous drainage and observe how VR impacted structural delineation during approach, resection, and overall strategic planning. The patient was a 30-yr-old female with no past medical history who presented with headaches and a generalized tonic clonic seizure. Workup included computed tomography, computed tomography angiography, magnetic resonance imaging, magnetic resonance angiography, and magnetic resonance venography; a high flow right frontal AVM was found. The AVM was safely resected using navigation integrated with VR; careful arterial devascularization preceded resection of the draining veins and then the AVM nidus. Postoperative scans confirmed complete resection of the AVM. This case outlines the application of a current state-of-the-art VR platform to assist the craniotomy for resection of an AVM.